Implementation of Guidance and Counseling Service Management System at SMPN 15 Mataram - Naya Safitri; Aditra Wahyuda; Mohamad Mustari (Public Service: Jurnal Ilmu Sosial dan Pendidikan, 2025)
The implementation of Guidance and Counseling (GC) services in schools plays a crucial role in assisting students in dealing with developmental, academic, social, and emotional challenges, especially in the digital era where behavioral changes among adolescents are becoming increasingly complex. This condition requires a well-planned, structured, and needs-based management system for GC services. Based on this urgency, this study aims to describe the implementation of the management system of Guidance and Counseling services at SMPN 15 Mataram, including program planning, forms of coordination among related parties, and the obstacles encountered during its implementation. This research employed a descriptive qualitative approach with data collected through in-depth interviews, direct observations, and documentation. The findings indicate that the GC program is planned based on the Student Needs Assessment Questionnaire (AKPD), enabling the services to remain flexible and relevant to students’ needs. The implementation includes individual counseling, classroom guidance, case assistance, and student development activities. Coordination among the GC teacher, homeroom teachers, subject teachers, and parents runs effectively through open and continuous communication. The challenges encountered mainly relate to the diversity of student characteristics and the influence of social media on adolescent behavior. This study contributes as an evaluation reference and provides insights for improving GC management to be more adaptive and responsive to the dynamics of students’ development.